Concept of Viral Inhibitors via NTCP - Fukano, Kento; Tsukuda, Senko; Watashi, Koichi; Wakita, Takaji (Seminars in liver disease, 2019)
Identification of sodium taurocholate cotransporting polypeptide (NTCP) as an entry receptor for hepatitis B and D viruses (HBV and HDV) has not only promoted our understanding of the mechanism underlying the viral entry process, but also provided cell culture models supporting viral infection. These models have greatly facilitated cell-based chemical screening for the discovery of entry inhibitors, and mode of action studies using such inhibitors have shown the advantages of NTCP as a drug target. Furthermore, in vitro chemical screening by application of high-throughput affinity-based technologies that target NTCP has identified a variety of unique small molecules that interfere with viral entry. This review summarizes this hot topic in the development of HBV/HDV entry inhibitors, with special focus on the use of NTCP as a drug target.